Estudio de prefactibilidad para la instalación de una planta procesadora de filetes de trucha (Oncorhynchus mykiss) en crema de verduras ready to eat - Zambrana Hinojosa, Marcia Isabel (2020)
The present research project aims to demonstrate that the installation of a trout fillet on vegetable cream ready to eat plant is economically and technologically viable. A market study was developed for this project and a potential market was obtained with acceptance of a product derived from trout, which represents 174 109 units of product for the first year After this analysis, the possible installation sites of the plant were evaluated, to start production, which is detailed in the plant location chapter. From which, the city of Huancayo, in the industrial district of El Tambo, was obtained as an optimal location. Then, the engineering analysis was developed to determine the ideal technology for the project (machines, equipment, production program and the maximum capacity of the plant), to evaluate the possibility of meeting the demand found. Based on this, the total area of the land was determined, which will consist of 608 m2 and the distribution of the areas was made according to the relational analysis, for greater productivity and resource use. According to investment criteria, the project provides an economic NPV of S/ 582 482,80; with an economic IRR of 27% and NPV Financial S/ 802 655,75; a financial IRR of 40%. These results indicate that the project is viable and profitable in both scenarios.